Características químicas e morfológicas da cerâmica arqueológica de Caxiuanã - Martins, Vítor Nazareno da Mata (Museu Paraense Emílio Goeldi, 2023)
Caxiuanã is located 400km, as the crow flies, west of Belém, in the municipalities of Portei and Melgaço, Pará. In this region 28 archaeological sites have been recorded to date, most of them located on the shores of the bay of Caxiuanã, rivers and streams. The objective of this work is to compare the morphological characteristics of the pottery from the regions of Santarém, Xingu and Marajó with those from Caxiuanã. Chemical and mineralogical analyses of pottery fragments from Caxiuanã are also being carried out. Morphological analysis of Caxiuanã pottery is being carried out and the morphological characteristics of the pottery from the other mentioned regions are being verified through bibliographic research. Ca, Mg, Zn, Mn and P will be analyzed in the Caxiuanã ceramic samples using atomic absorption and colorimetric apparatuses. The Caxiuanã pottery is presenting, up to now, as the predominant antiplastic the cariape, followed by sand and cauixi. The most frequently found decoration is white, followed by red, with incised, excised and modeled decoration occurring less frequently. In the Santarém pottery there is a predominance of sand as an antiplastic, followed by cauixi, ground sherd and cariapé, while in the Konduri the Cauixi is more frequent. As for decoration, in the Xingu one can observe painted, incised, modeled, dotted and typed decoration. At Santarém the decoration with dichromatic and trichromatic paintings prevails, and the Konduri presents straight incisions with rare traces of red painting and a high frequency of modeled.